1992
DOI: 10.1007/bf00006080
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of five cladoceran species in short- and long-term copper exposure

Abstract: The study was carried out to assess the effect of both short-and long-term copper exposure on five cladoceran species differing in body size and habitat, i.e. Daphnia magna, D. pulex, D. galeata, Bosmina longirostris, and Chydorus sphaericus. The species-specific 48 h EC,, values for fed neonates were used to determine the chronic exposure levels (52% and 65% of the EC,, values). The experiment was run at two food levels. Long-term copper exposure retarded growth in each of the species studied. However, the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
2
3

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(85 citation statements)
references
References 36 publications
(47 reference statements)
3
77
2
3
Order By: Relevance
“…Due to these positive effects the population growth rate of food-limited midges increased significantly by exposure to 2.0 and 5.6 Ixg Cd/L compared to the food-limited control. In experiments with five cladoceran species Koivisto et al (1992) obtained comparable results determining the effects of copper on the intrinsic rate of increase at two food levels. Only for Daphnia galeata and Bosmina longirostris was food limitation so severe that mortality increased due to food limitation.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Due to these positive effects the population growth rate of food-limited midges increased significantly by exposure to 2.0 and 5.6 Ixg Cd/L compared to the food-limited control. In experiments with five cladoceran species Koivisto et al (1992) obtained comparable results determining the effects of copper on the intrinsic rate of increase at two food levels. Only for Daphnia galeata and Bosmina longirostris was food limitation so severe that mortality increased due to food limitation.…”
Section: Discussionmentioning
confidence: 81%
“…However, the food in these experiments was not very limited, because mortality was not or only slightly increased compared to the unexposed animals. Koivisto et al (1992) studied the chronic toxicity of copper to five cladoceran species at two food levels. For two species food limitation was so severe that it increased the mortality of the unexposed, food-limited animals.…”
mentioning
confidence: 99%
“…Long-term exposure to elevated Cu levels can reduce growth rate in Bosmina (Koivisto et al, 1992), and similarly, Cu and Ni exposure can reduce growth rate in the cladoceran genus Daphnia (Ingersoll and Winner, 1982;Münzinger, 1990), leading to smaller individuals at maturity. Contamination with Cu and Ni has previously been identified as an important factor structuring the cladoceran species assemblages in these lakes, with assemblages experiencing more pronounced shifts in Sudbury lakes, relative to those in Killarney (Labaj et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found effects on food availability and metal toxicity. For example, in acute toxicity tests, Chandini (1988) found that the cladocerans D. carinata and Echinisca triserialis were more sensitive to cadmium as food levels decreased, and Koivisto et al (1992) found that in five cladoceran species (D. magna, D. pulex, D. galeata, Bosmina longirostris, and Chydorus sphaericus), copper exposure at low food levels decreased survival compared to high food levels. Further, although a sufficient amount of food may be available, it may still be of too low quality, which may have a negative impact on growth and reproduction (Li et al 2008, Dahl et al 2009).…”
Section: Environmental Factors Of Importance For Uptake and Effectsmentioning
confidence: 99%